2011
DOI: 10.1111/j.1755-148x.2011.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

The gluttonous side of malignant melanoma: basic and clinical implications of macroautophagy

Abstract: Summary True to their inherent aggressive behavior, melanomas keep impressing the melanoma community with their ability to bypass tumor suppressor mechanisms. Name a pathway with the potential to control cell survival and melanoma cells will likely have it potentiated by multiple genetic or epigenetic alterations. In the context of progression and chemoresistance, large efforts have been dedicated to the identification of protective mechanisms associated with or linked to apoptotic death programs. These studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 123 publications
0
25
0
Order By: Relevance
“…A better knowledge of genetic and pharmacological modulators of autophagy would have important basic and clinical implications for cutaneous melanoma. Histological studies revealed a great intra and inter-tumoral variability in multiple autophagy genes (5). One of the most intriguing changes in expression relates to the autophagy factor, autophagy related gene 5 (ATG5), a key player in autophagosome formation.…”
Section: Introductionmentioning
confidence: 99%
“…A better knowledge of genetic and pharmacological modulators of autophagy would have important basic and clinical implications for cutaneous melanoma. Histological studies revealed a great intra and inter-tumoral variability in multiple autophagy genes (5). One of the most intriguing changes in expression relates to the autophagy factor, autophagy related gene 5 (ATG5), a key player in autophagosome formation.…”
Section: Introductionmentioning
confidence: 99%
“…While immunochemistry of normal human melanocytes revealed low expression of LC3 protein, a histological MA marker, focal staining of LC3 molecules increased in spreading subcutaneous melanoma consistent with increased tumor MA (Checinska and Soengas, 2011; Corazzari et al, 2013). Immunohistochemical analysis of early and late stage melanomas revealed that late stage tumors associated with poor prognosis, expressed reduced levels of p62, a protein whose turnover is linked to enhanced MA (Ellis et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…11,27 The specific contribution of other lysosomal-associated processes such as (macro)autophagy to melanoma initiation, progression and response to therapy is still under evaluation. 28,29 Melanomas are long known for their ability to induce autophagosome formation in response to a variety of endogenous stressinducing factors (e.g., deregulated BRAF>MAPK oncogenic signals) [30][31][32] and external cues (including hypoxia, nutrient deprivation, and a broad spectrum of therapeutic agents, among many others). 29,33,34 However, lysosomal-dependent degradation may favor or inhibit cell survival, depending on the identity and/or duration of the stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…29,33,34 However, lysosomal-dependent degradation may favor or inhibit cell survival, depending on the identity and/or duration of the stimuli. 28,29 Mechanisms underlying these dual functions remain unclear. Multitumor genomic or transcriptomic profiles have not been performed to determine whether melanomas can regulate or target autophagy factors in a lineage-specific manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation